Claspin recruits Cdc7 kinase for initiation of DNA replication in human cells - Chi-Chun Yang (Nature Portfolio, 2016)
Claspin mediates the transmission of a replication-stress signal from ATR to Chk1 and is necessary for efficient fork progression. Here the authors demonstrate that the C-terminal acidic patch is important for this role due to its interaction with Cdc7.